Biomarkers of local inflammation at the skin's surface may predict both pressure and diabetic foot ulcers - Wilson, Pauline; Patton, Declan; O'Connor, Tom; Boland, Fiona; Budri, Aglecia Mv [UNESP]; Moore, Zena; Phelan, Niamhe (Mark Allen Group, 2024)
This commentary considers the similarities which exist between pressure ulcers (PUs) and diabetic foot ulcers (DFUs). It aims to describe what is known to be shared - both in theory and practice - by these wound types. It goes on to detail the literature surrounding the role of inflammation in both wound types. PUs occur following prolonged exposure to pressure or pressure in conjunction with shear, either due to impaired mobility or medical devices. As a result, inflammation occurs, causing cell damage. While DFUs are not associated with immobility, they are associated with altered mobility occurring as a result of complications of diabetes. The incidence and prevalence of both types of lesions are increased in the presence of multimorbidity. The prediction of either type of ulceration is challenging. Current risk assessment practices are reported to be ineffective at predicting when ulceration will occur. While systemic inflammation is easily measured, the presence of local or subclinical inflammation is harder to discern. In patients at risk of either DFUs or PUs, clinical signs and symptoms of inflammation may be masked, and systemic biomarkers of inflammation may not be elevated sufficiently to predict imminent damage until ulceration appears. The current literature suggests that the use of local biomarkers of inflammation at the skin's surface, namely oedema and temperature, may identify early tissue damage.